Field trials reveal trade-offs between grain size and grain number in wheat ectopically expressing a barley sucrose transporter - Susanne Brunner; Heiko Weichert; Michael Meissle; Jörg Romeis; Hans Weber (Field Crops Research, 2024)

Trap crops enhance the control efficacy of Metarhizium brunneum against a soil-dwelling pest - Michael Brunner; Christiane Zeisler; Diane Neu; Claire Rotondo; Oskar R. Rubbmark; Lara Reinbacher; Giselher Grabenweger; Michael Traugott (Journal of Pest Science, 2024)
Soil-dwelling insect pests may cause considerable damage to crops worldwide, and their belowground lifestyle makes them hard to control. Amongst the most promising control agents for subterranean pests are soilborne entomopathogenic fungi (EPF) such as Metarhizium brunneum . Albeit EPF can be highly pathogenic to their target pest species under laboratory conditions, their efficacy in the field is often limited due to adverse environmental conditions. Here, we test for the first time if the efficacy of EPF can be improved when they are augmented with trap crops. In a field experiment, the M. brunneum strain ART2825 was combined with a trap crops mixture of six plant species and evaluated for its control effect of wireworms (Coleoptera: Elateridae). When both were combined in the main crop, potato damage was lowered on average by 42.5% and wireworm abundance by 50.8%. Single application of trap crops or EPF lowered damage/pest abundance only by 29.9%/15.89% and 34.7%/4.77%, respectively. Importantly, the strength of the synergistic pest control effect between trap crops and EPF increased disproportionately with increasing wireworm abundance. However, DNA-based gut content analysis showed that wireworms’ feeding preferences were not shifting toward the trap crops. Our findings demonstrate that combining trap crops with EPF improves the efficacy of the latter and leads to a synergistic control effect which magnifies with increasing wireworm abundance. Hence, the synergistic effect of EPF and trap crops might be a promising control strategy for soil-dwelling pests in general and significantly improve our abilities to manage soil pests environmentally friendly.

Artificial intelligence to improve ischemia prediction in Rubidium Positron Emission Tomography—a validation study - Simon M. Frey; Adam Bakula; Andrew Tsirkin; Vasily Vasilchenko; Peter Ruff; Caroline Oehri; Melissa Fee Amrein; Gabrielle Huré; Klara Rumora; Ibrahim Schäfer; Federico Caobelli; Philip Haaf; et al. (EPMA Journal, 2023)
Background Patients are referred to functional coronary artery disease (CAD) testing based on their pre-test probability (PTP) to search for myocardial ischemia. The recommended prediction tools incorporate three variables (symptoms, age, sex) and are easy to use, but have a limited diagnostic accuracy. Hence, a substantial proportion of non-invasive functional tests reveal no myocardial ischemia, leading to unnecessary radiation exposure and costs. Therefore, preselection of patients before ischemia testing needs to be improved using a more predictive and personalised approach. Aims Using multiple variables (symptoms, vitals, ECG, biomarkers), artificial intelligence–based tools can provide a detailed and individualised profile of each patient. This could improve PTP assessment and provide a more personalised diagnostic approach in the framework of predictive, preventive and personalised medicine (PPPM). Methods Consecutive patients ( n = 2417) referred for Rubidium-82 positron emission tomography were evaluated. PTP was calculated using the ESC 2013/2019 and ACC 2012/2021 guidelines, and a memetic pattern–based algorithm (MPA) was applied incorporating symptoms, vitals, ECG and biomarkers. Five PTP categories from very low to very high PTP were defined (i.e., < 5%, 5–15%, 15–50%, 50–85%, > 85%). Ischemia was defined as summed difference score (SDS) ≥ 2. Results Ischemia was present in 37.1%. The MPA model was most accurate to predict ischemia (AUC: 0.758, p < 0.001 compared to ESC 2013, 0.661; ESC 2019, 0.673; ACC 2012, 0.585; ACC 2021, 0.667). Using the < 5% threshold, the MPA’s sensitivity and negative predictive value to rule out ischemia were 99.1% and 96.4%, respectively. The model allocated patients more evenly across PTP categories, reduced the proportion of patients in the intermediate (15–85%) range by 29% (ACC 2012)–51% (ESC 2019), and was the only tool to correctly predict ischemia prevalence in the very low PTP category. Conclusion The MPA model enhanced ischemia testing according to the PPPM framework: The MPA model improved individual prediction of ischemia significantly and could safely exclude ischemia based on readily available variables without advanced testing (“predictive”). It reduced the proportion of patients in the intermediate PTP range. Therefore, it could be used as a gatekeeper to prevent patients from further unnecessary downstream testing, radiation exposure and costs (“preventive”). Consequently, the MPA model could transform ischemia testing towards a more personalised diagnostic algorithm (“personalised”).

Combining entomopathogenic Pseudomonas bacteria, nematodes and fungi for biological control of a below-ground insect pest - Anna Spescha; Joana Weibel; Lara Wyser; Michael Brunner; Mathias Hess Hermida; Aurélie Moix; Franziska Scheibler; Anouk Guyer; Raquel Campos-Herrera; Giselher Grabenweger; Monika Maurhofer (Agriculture, Ecosystems & Environment, 2023)

Silicification patterns in wheat leaves related to ontogeny and soil silicon availability under field conditions - Jörg Schaller; Daniel Puppe; Jaqueline Busse; Silvia Paasch; Ofir Katz; Eike Brunner; Danuta Kaczoreck; Michael Sommer (Plant and Soil, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Soil fauna drives vertical redistribution of soil organic carbon in a long‐term irrigated dry pine forest - Claudia Guidi; Beat Frey; Ivano Brunner; Katrin Meusburger; Michael E. Vogel; Xiaomei Chen; Tobias Stucky; Dariusz J. Gwiazdowicz; Piotr Skubała; Arun K. Bose; Marcus Schaub; Andreas Rigling; et al. (Global Change Biology, 2022)
Summer droughts strongly affect soil organic carbon (SOC) cycling, but net effects on SOC storage are unclear as drought affects both C inputs and outputs from soils. Here, we explored the overlooked role of soil fauna on SOC storage in forests, hypothesizing that soil faunal activity is particularly drought‐sensitive, thereby reducing litter incorporation into the mineral soil and, eventually, long‐term SOC storage. In a drought‐prone pine forest (Switzerland), we performed a large‐scale irrigation experiment for 17 years and assessed its impact on vertical SOC distribution and composition. We also examined litter mass loss of dominant tree species using different mesh‐size litterbags and determined soil fauna abundance and community composition. The 17‐year‐long irrigation resulted in a C loss in the organic layers (−1.0 kg C m −2 ) and a comparable C gain in the mineral soil (+0.8 kg C m −2 ) and thus did not affect total SOC stocks. Irrigation increased the mass loss of Quercus pubescens and Viburnum lantana leaf litter, with greater effect sizes when meso‐ and macrofauna were included (+215%) than when excluded (+44%). The enhanced faunal‐mediated litter mass loss was paralleled by a many‐fold increase in the abundance of meso‐ and macrofauna during irrigation. Moreover, Acari and Collembola community composition shifted, with a higher presence of drought‐sensitive species in irrigated soils. In comparison, microbial SOC mineralization was less sensitive to soil moisture. Our results suggest that the vertical redistribution of SOC with irrigation was mainly driven by faunal‐mediated litter incorporation, together with increased root C inputs. Our study shows that soil fauna is highly sensitive to natural drought, which leads to a reduced C transfer from organic layers to the mineral soil. In the longer term, this potentially affects SOC storage and, therefore, soil fauna plays a key but so far largely overlooked role in shaping SOC responses to drought.

Calendar age and puberty-related development of regional gray matter volume and white matter tracts during adolescence - Ayaka Ando; Peter Parzer; Michael Kaess; Susanne Schell; Romy Henze; Stefan Delorme; Bram Stieltjes; Franz Resch; Romuald Brunner; Julian Koenig (Brain Structure and Function, 2021)
Background Adolescence is a critical time for brain development. Findings from previous studies have been inconsistent, failing to distinguish the influence of pubertal status and aging on brain maturation. The current study sought to address these inconsistencies, addressing the trajectories of pubertal development and aging by longitudinally tracking structural brain development during adolescence. Methods Two cohorts of healthy children were recruited (cohort 1: 9–10 years old; cohort 2: 12–13 years old at baseline). MRI data were acquired for gray matter volume and white matter tract measures. To determine whether age, pubertal status, both or their interaction best modelled longitudinal data, we compared four multi-level linear regression models to the null model (general brain growth indexed by total segmented volume) using Bayesian model selection. Results Data were collected at baseline ( n = 116), 12 months ( n = 97) and 24 months ( n = 84) after baseline. Findings demonstrated that the development of most regional gray matter volume, and white matter tract measures, were best modelled by age. Interestingly, precentral and paracentral regions of the cortex, as well as the accumbens demonstrated significant preference for the pubertal status model. None of the white matter tract measures were better modelled by pubertal status. Limitations: The major limitation of this study is the two-cohort recruitment. Although this allowed a faster coverage of the age span, a complete per person trajectory over 6 years of development (9–15 years) could not be investigated. Conclusions Comparing the impact of age and pubertal status on regional gray matter volume and white matter tract measures, we found age to best predict longitudinal changes. Further longitudinal studies investigating the differential influence of puberty status and age on brain development in more diverse samples are needed to replicate the present results and address mechanisms underlying norm-variants in brain development.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Physiological and phylogenetic variability of Mexican Metarhizium strains - Carolina Brunner-Mendoza; Soumya Moonjely; María del Rocío Reyes-Montes; Conchita Toriello; Michael Bidochka (BioControl, 2017)

Intraguild predation in pioneer predator communities of alpine glacier forelands - Lorna Raso; Daniela Sint; Rebecca Mayer; Simon Plangg; Thomas Recheis; Silvia Brunner; Rüdiger Kaufmann; Michael Traugott (Molecular Ecology, 2014)
Pioneer communities establishing themselves in the barren terrain in front of glacier forelands consist principally of predator species such as carabid beetles and lycosid spiders. The fact that so many different predators can co‐inhabit an area with no apparent primary production was initially explained by allochthonous material deposited in these forelands. However, whether these populations can be sustained on allochthonous material alone is questionable and recent studies point towards this assumption to be flawed. Intraguild predation ( IGP ) might play an important role in these pioneer predator assemblages, especially in the very early successional stages where other prey is scarce. Here, we investigated IGP between the main predator species and their consumption of C ollembola, an important autochthonous alternative prey, within a glacier foreland in the Ö tztal ( A ustrian A lps). Multiplex PCR and stable isotope analysis were used to characterize the trophic niches in an early and late pioneer stage over 2 years. Results showed that intraguild prey was consumed by all invertebrate predators, particularly the larger carabid species. Contrary to our initial hypothesis, the DNA detection frequency of IGP prey was not significantly higher in early than in late pioneer stage, which was corroborated by the stable isotope analysis. Collembola were the most frequently detected prey in all of the predators, and the overall prey DNA detection patterns were consistent between years. Our findings show that IGP appears as a constant in these pioneer predator communities and that it remains unaffected by successional changes.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Occurrence of Agriotes wireworms in Austrian agricultural land - Karin Staudacher; Nikolaus Schallhart; Peter Pitterl; Corinna Wallinger; Nina Brunner; Marion Landl; Bernhard Kromp; Johann Glauninger; Michael Traugott (Journal of Pest Science, 2013)

Ethyl pyruvate improves survival in awake hemorrhage - Bolin Cai; Michael Brunner; Haichao Wang; Ping Wang; Edwin A. Deitch; Luis Ulloa (Journal of Molecular Medicine, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cell migration through small gaps - Claudia A. Brunner; Allen Ehrlicher; Bernd Kohlstrunk; Detlef Knebel; Josef A. Käs; Michael Goegler (European Biophysics Journal, 2006)

Mechanisms of mitochondrial protein import - Mathias F. Bauer; Stefan Paschen; Walter Neupert; Michael Brunner (Protoplasma, 2000)

Rickettsial Relative Associated with Papaya Bunchy Top Disease - Michael J. Davis; Zhentu Ying; Bryan R. Brunner; Alberto Pantoja; Feiko H. Ferwerda (Current Microbiology, 1998)